Undertreatment of cardiovascular risk factors in the type 1 diabetes exchange clinic network (United States) and the prospective diabetes follow-up (Germany/Austria) registries - Shah, Viral N.; Grimsmann, Julia M.; Foster, Nicole C.; Dost, Axel; Miller, Kellee M.; Pavel, Marianne Ellen; Weinstock, Ruth S.; Karges, Wolfram; Maahs, David M.; Holl, Reinhard W. (Diabetes Obesity & Metabolism, 2020)
Aim To examine the control of cardiovascular risk factors in type 1 diabetes (T1D) registries from the United States and Germany/Austria.
CRIS-Team WoS Importer:2020-05-29